Perancangan Sistem Transaksi Laundry Berbasis Web Pada F&F Laundry - Wahyu Erlangga Susanto; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Information Technology is a study, design, implementation, development, support or management of computer-based information systems, especially in computer hardware and software applications. Transactions are events or situations that affect the company's financial position. Therefore F&F Laundry wants to develop a manual transaction system to be website-based. The design of this website uses the Watetfall method in its work, namely creating a website to assist transactions at F&F Laundry, which produces a system that displays laundry transaction data. The result will be a website to help transactions at F&F Laundry, which produces a system that displays laundry transaction data.